Effects of Lentilactobacillus buchneri and chemical additives on fermentation profile, chemical composition, and nutrient digestibility of high-moisture corn silage - Wang, Lei; Bao, Jinze; Zhuo, Xingliang; Li, Yingqi; Zhan, Wenyuan; Xie, Yixiao; Wu, Zhe; Yu, Zhu (Frontiers in Veterinary Science, 2023)
High-moisture corn silage presents a novel approach to reduce forage feeding expenses and enhance animal performance. Nevertheless, given corn's proclivity for starch, suboptimal fermentation quality in high-moisture corn silage can lead to spoilage, posing risks to livestock well-being. Therefore, the objective of this study is to evaluate the effects of different additives on the fermentation profile, chemical composition, nutrient digestibility of high-moisture corn (HMC) silage. All treatments improved the quality of high-moisture corn silage fermentation, as demonstrated by a decrease in pH and increase in lactic acid (LA) content. The high-moisture corn silage had a low content of trans fatty acids (TFA). Fermentation effectively decreased prolamin content while increasing 48-hour in vitro dry matter digestibility (IVDMD), estimated total tract starch digestibility (eTTSD), total digestible nutrient (TDN), and relative grain quality (RGQ) of high-moisture corn silage. Nonetheless, no effect was observed on the 48-hour IVDMD of high-moisture corn silage among the different treatments. Pearson's correlation analysis indicated that neutral detergent fiber (aNDF), neutral detergent insoluble protein (NDIP), crude protein (CP), zein, and prolamin closely correlated with the digestibility of high-moisture corn. The study's findings demonstrate that inoculating L. buchneri and potassium sorbate can improve the quality of high-moisture corn silage fermentation and digestibility in different hybrids. The results will provide insights for enhancing farm productivity and profitability in China.